Serviços de iniciação de pagamentos - Costa, Jacinto Duarte Afonso (2018)
The present thesis is focused on identified issues from the banking industry, namely the absence of a common interface for all banks; issues related to security; or the intermediaries’ dependency for purchases. Several bodies are significantly investing in order to resolve these challenges. Among them, one may highlight the European Commission, which proposes the use of an Application Program Interface (API) centralised for all e-banking services. This API was suggested through the Revised Payment Service Directive (PSD2). In this thesis, the issues identified were taken into account, and an effort was made to overcome them through the use of the PSD2. The PSD2 directive was introduced by the European Commission to resolve many issues in the banking industry. We explored the PSD2 directive through a case study focused on creating an intermediary payment, and its incorporation in an e-commerce website. An payment system called NearSoft Payment Provider (NPP) was implemented. It is easily integrable into a website through a set of widgets, which allows payments through a transactions’ request under the PSD2 directive. In addition, other features such as payment management between different accounts, purchase history visualization, and payment security mechanisms were added. During the development we had the concern of making the platform as easy as possible when it comes to its expansion, integration and maintenance. There was as well the concerb on properly documenting all the developed code. The approach taken was tested according to its usability (8 participants) and ease of integration (2 programmers/developers), producing encouraging results. However, additional tests will be needed in order to prove the validity of the solution proposed.